2006
DOI: 10.1007/11815921_17
|View full text |Cite
|
Sign up to set email alerts
|

Fast Suboptimal Algorithms for the Computation of Graph Edit Distance

Abstract: Graph edit distance is one of the most flexible mechanisms for error-tolerant graph matching. Its key advantage is that edit distance is applicable to unconstrained attributed graphs and can be tailored to a wide variety of applications by means of specific edit cost functions. Its computational complexity, however, is exponential in the number of vertices, which means that edit distance is feasible for small graphs only. In this paper, we propose two simple, but effective modifications of a standard edit dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
147
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(148 citation statements)
references
References 12 publications
0
147
0
1
Order By: Relevance
“…Two adaptations of the A algorithm were proposed in [187]. The path length A approach introduces an additional weighting to the A algorithms optimal path and heuristic cost functions to avoid expanding the search tree when a node with a significantly large cost is encountered during vertex mapping.…”
Section: Graph Edit Distancementioning
confidence: 99%
See 3 more Smart Citations
“…Two adaptations of the A algorithm were proposed in [187]. The path length A approach introduces an additional weighting to the A algorithms optimal path and heuristic cost functions to avoid expanding the search tree when a node with a significantly large cost is encountered during vertex mapping.…”
Section: Graph Edit Distancementioning
confidence: 99%
“…The beam search A algorithm approach [187] generates a smaller set of sequences demonstrated that the beam search approach was almost as accurate as a brute force approach when using large beams [187]. When applied to a classification task, the suboptimality of the algorithm resulted in an increase in inter-class differences while intra-class differences were not strongly affected, demonstrating that the algorithm was appropriate for ranking objects images based on similarity of their classes.…”
Section: Graph Edit Distancementioning
confidence: 99%
See 2 more Smart Citations
“…In our case, the set of prototypes is exactly the same set S = {g 1 , g 2 , ..., g n } of training graphs that are used to compute the median graph. We therefore compute the graph edit distance between every pair of graphs in the set S. Since computing the graph edit distance is a NP-complete problem, in this work we have used the suboptimal methods presented in [21,22]. The resulting distances are arranged in a distance matrix.…”
Section: Graph Embeddingmentioning
confidence: 99%